Effect of cetylpyridinium chloride with xylitol on the formation of biofilm and development of gingivitis - Bruna Ghiraldini; Erika Tie Furushima; Renato Corrêa Viana Casarin; Karina Teixeira Villalpando (Universidade Estadual de Campinas, 2015)
Aim: To assess the effect of the combination of cetylpyridinium chloride and xylitol on the formation of dental biofilm and development of experimental gingivitis. Methods: A crossover, double-blind, placebo-controlled study was conducted and divided into two phases of 21 days each with a time interval of 10 days between them. A modified experimental gingivitis model was used and 31 volunteers were randomly divided into 2 groups. The volunteers performed daily mouthwashes twice a day with the test solution containing cetylpyridinium combined with xylitol or a placebo solution. On day 0 and day 21 of each phase the Plaque Index (PI) and Gingival Index (GI) of each volunteer were measured. During this phase, the volunteers brushed their teeth with standard toothbrushes and dentifrice, protecting the third quadrant with a toothshield. After brushing, the toothshield was removed and the mouthwash was used. Results: The PI values observed in the Test Group at baseline and on day 21 were 0 (0.00 - 0.03) and 0 (0.22-0.48) respectively, and in Control Group 0 (0.00 - 0.03) and 1 (0.45 - 0.81) (inter-group analysis - McNemar test, p<0.05). For GI, the values obtained in the Test Group were 0 (0.00 - 0.03) and 1 (0.48 - 0.71), at baseline and day 21 and in Control Group 0 (0.00 - 0.03) and 1 (0.58 - 0.84) (inter-group analysis - McNemar test, p>0.05). Conclusions: The test solution had a positive effect on dental biofilm control. However, it was not capable of preventing the development of experimental gingivitis.